The Role of Universities in Supporting Media for Household and Environmental Health Education: Peran Perguruan Tinggi Dalam Pendampingan Media Penyuluhan Kesehatan Rumah Tangga dan Lingkungan - Putri, Lusi Dwi Putri; Imbardi; Apriliana Hidayati Nurdin; Repi, Repi; Aidil Hamka Siregar; Putri, Rizki Martin Situmorang (Universitas Lancang Kuning, 2025)
Canva is a graphic design application that bridges its users to easily design various types of creative materials online. Starting from designing greeting cards, posters, brochures, infographics, to presentations. Canva is currently available in several versions, namely the web, iPhone, and Android versions. In times like today, educational institutions provide lessons on how to design something to support teaching and learning activities, one of which is Higher Education. One example of community service made by Higher Education is providing training to the community or more precisely, health workers as a form of practice of the knowledge that has been given. This training activity also aims to make health workers more mature and ready to design posters or pamphlets related to household and environmental health as well as about the use of drugs. The results obtained are partners understand how to use the Canva graphic design application, from 25 (twenty-five) participants with a 'Very Good' score of 12%, a 'Good' score of 60%, a 'Medium' score of 28% and a 'Not Shown' score of 0%. Other results included teaching materials on Canva Graphic Design and an article for the Community Service Journal. The findings revealed increased partner capacity in using the Canva Graphic Design application.